Accurate prenatal discrimination of placenta accreta spectrum from uterine dehiscence is necessary to ensure optimal management. Issue 7 (9th July 2021) - Adu-Bredu, Theophilus Kofi; Owusu-Bempah, Atta; Collins, Sally
Abstract : Uterine scar dehiscence with underlying placenta is often misdiagnosed as placenta accreta spectrum both prenatally and intraoperatively due to the absence of myometrial tissue in the area. Misdiagnosis generates obstetric anxiety and results in overtreatment which carries a risk of iatrogenic injury. We present a case of the antenatal diagnosis of uterine dehiscence in a 36-year-old woman with a history of two caesarean deliveries and a low-lying placenta. We further describe the sonographic features useful for differentiating this condition from placenta accreta spectrum in instances where the placenta lies under an area of full thickness uterine scar dehiscence.